SOLAR WIND SPEED AND ULF Pc5 POWER AT LOW-LATITUDE AS PRECURSOR OF ELECTRON FLUX ENHANCEMENT DUE TO GEOEFFECTIVE CMEs IN 2015 TO 2017 - Siska Filawati; Fitri Nuraeni (Jurnal Sains Dirgantara, 2019)
Electron flux is one of the space weather parameters that needs to be monitored and predicted for the purpose of mitigating the negative effects of space weather. Solar storms caused by CME which will affect electron flux can be observed using spacebased and ground-based data. The spacebased data used is solar wind speed data from ACE satellite and electron flux from GOES 13 satellite. The groundbased data are magnetometer data from Biak and Parepare stations which will be calculated on Pc5 power values. Cross correlation method is used to determine the correlation of two equations as functions that influence each other as electron flux which is affected by solar wind speed and Pc5 power. The correlation value of the speed of solar wind with electron flux is higher than Pc5 power with electron flux. However, the maximum value of r power Pc5 with electron flux occurs before the maximum value of r solar wind speed with electron flux which means that Pc5 power is more effective as a precursor to electron flux enhancement.